Risk factors for the alzheimer's disease. Systematic review and meta-analysis - G. R. Khasanova; M. Sh. Muzaffarova (Фундаментальная и клиническая медицина, 2024)
The “aging” of the population increased the importance of researches in the field of the epidemiology of chronic diseases, including Alzheimer's disease (AD) -the most common cause of dementia in the population.Aim. The role of potential risk factors for AD through a systematic review and meta-analysis. The “aging” of the population has updated research in the field of the epidemiology of chronic diseases, incl. Alzheimer's disease (AD) is the most common cause of dementia in the population. The aim of the study was to assess the role of potential risk factors for AD through a systematic review and meta-analysis.Materials and Methods. Using the electronic databases PubMed, Scopus, E-library, a search was made for articles in Russian and English, published from 1995 to 2022. In accordance with the clinical question, using the PECO formula, papers were selected in which the authors investigated the role of various risk factors in groups with and without AD. The study was carried out in accordance with the international guidelines for writing systematic reviews and meta-analyses "PRISMA". Study quality was analyzed using the Newcastle-Ottawa scale for cohort and case-control studies. The degree of heterogeneity was assessed using the chi-square test and the I2 coefficient. Publication bias was analyzed using a funnel plot. We used the software Review Manager 5.3 and Microsoft Office Excel 2010.Results. Initially, 3197 articles were retrieved from the databases; After screening and eligibility analysis, 17 studies were included in the me-ta-analysis (11 case-control studies and 6 cohort studies). Totally, these publications included data from 134,732 people with a confirmed diagnosis of AD and 1,058,143 respondents without AD (control group). According to the results of the meta-analysis, significant risk factors were: heredity (odds ratio (OR) 1.82; 95% confidence interval (95% CI) 1.66-1.99), arterial hypertension (OR 1.65; 95% CI 1.29-2.13), hypercholesterolemia (OR 1.25; 95% CI 1.13-1.38), obesity (OR 1.13; 95% CI 1.09-1.17), presence of diabetes mellitus 2 type (OR 1.36; 95%; CI 1.15-1.62), low level of education (OR 1.61; 95% CI 1.18-2.18), depression (OR 1.35; 95% CI 1.03-1.76). There was no relationship with alcohol consumption, smoking, a history of myocardial infarction and / or coronary heart disease, a history of acute cerebrovascular accident, insomnia, female gender, traumatic brain injury.Conclusion. The conducted meta-analysis allowed to obtain confirmation of the role of various potential risk factors for AD; at the same time, many of them are modifiable and are associated with metabolic disorders, which can probably be involved into the process of accumulation and deposition of beta-amyloid in the cells of the nervous system. Continued research on this issue could contribute to the development of prognostic scales and personalized recommendations for the prevention of this currently incurable disease.